The determinants of sexual-risk behaviour among incarcerated adolescents in Malaysia - a mixed methods study / Nik Daliana binti Nik Farid - Nik Farid, Nik Daliana (2013)
The purpose of this study was to determine the proportion of sexual-risk behaviour (SRB) and its associated factors among incarcerated adolescents within the Malaysian welfare-institution system. This group of adolescents were chosen because they had been identified as participating in SRBs, so using them would facilitate identification of determinants involved. The study employed a sequential, mixed-method approach that combined qualitative and quantitative data. Quantitative data was collected using a self-administered questionnaire; variables used in the questionnaire were identified from applying the Social Ecological Model (SEM). The qualitative phase consisted of in-depth interviews and written essays. The questionnaires were completed by 1082 adolescents, while 29 participants were interviewed and wrote essays. All participants were recruited from 22 welfare institutions in Peninsular Malaysia, were between 12 and 19 years old and comprised 86.9% Malay, 8.5% Indian and 3.5% Chinese. Overall, 62.3% of incarcerated adolescents had engaged in sexual intercourse. The mean age at first sexual intercourse for both genders was 14 years. Sexual intercourse in the study population was associated with individual factors such as female gender (OR = 1.75, 95% CI = 1.11–2.74), alcohol use (OR = 1.80, 95% CI = 1.10–2.94), illicit drug use (OR = 1.85, 95% CI = 1.07–3.22), permissive attitude toward premarital sex (OR = 4.34, 95% CI = 2.17–8.70), a history of child sexual abuse (OR = 5.41, 95% CI = 3.52–8.32) and viewing pornography (OR = 2.84, 95% CI = 1.65–4.89). Among the study subjects who had initiated sex, 55.1% were found to have engaged in SRBs. The qualitative findings showed that belief in “sex as an expression of love” was a strong reason for initiating sexual intercourse. This finding was further confirmed by methodological triangulation. The study recommends that sexual and reproductive health (SRH) programmes focusing on individual determinants of sexual initiation and SRB should be developed for adolescents in Malaysia.